Can Adventurous Training Have a Role in Improving Clinical Outcomes?. Issue 2 (1st June 2012) - Mellor, Adrian; Jackson, S; Hardern, R
Abstract : The aim of military adventurous training (AT) is "to develop, through authorised challenging pursuits and within an outdoor environment, leadership and the qualities necessary to enhance the performance of military personnel during peace and war" . An increasing amount of effort is being applied by all three services to increase participation in AT to achieve these, largely immeasurable, aims. Existing guidance to Commanding Officers dictates that, where possible, 20% of a unit strength should undertake some form of AT annually with 5% taking part in an overseas expedition. In a speech in 2008 Alan Johnson, the then Secretary of State for Health, acknowledged that for Armed Forces medical personnel "just as important as clinical skills are issues such as leadership, communication, adaptability and teamwork ." Controlled exposure to risk, discomfort and personal hardship is a common theme for both AT activities and military deployments. Both General Medical Council competencies for all doctors and the Royal College of Anaesthetists military module include elements which can effectively be taught and developed through training in an outdoors environment. These skills include communication skills, leadership, risk assessment and interdisciplinary working. In this review the value of AT in training doctors to develop those attributes is examined.